Pendampingan Strategis Penyusunan Renstra Perangkat Daerah yang Terpadu dengan RPJMD Merauke 2025–2029 - Indra Kertati; Fadhli Rizal Makarim; Karningsih Karningsih (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The formulation of Strategic Plans (Renstra) aligned with the Regional Medium-Term Development Plan (RPJMD) is a crucial component in regional development planning systems. However, many local government agencies face institutional and technical challenges in producing high-quality, integrated Renstra documents. This community engagement program aimed to assist local government agencies in Merauke Regency in developing Renstra documents aligned with the 2025–2029 RPJMD using a Participatory Action Research (PAR) approach. The activity was conducted in four groups representing basic service, administrative, technical, and regional management functions. The PAR method was applied to foster active involvement of government staff in identifying strategic issues, setting goals and targets, formulating performance indicators, and determining priority programs. The results showed that the participatory approach effectively improved technical understanding and promoted awareness of result-based planning. Despite challenges such as limited human resources and sectoral data, most agencies successfully developed more structured and responsive Renstra documents. The process also promoted a collaborative dialogue culture between academia and bureaucracy. This program concludes that PAR can serve as an effective model for improving the quality of strategic planning documents and strengthening institutional capacity in regional governments. Recommendations include the need for sustainable capacity-building programs, the formation of internal facilitator teams, and stronger integration between planning and budgeting systems